2017
DOI: 10.1080/10410236.2016.1278506
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record (EHR) Organizational Change: Explaining Resistance Through Profession, Organizational Experience, and EHR Communication Quality

Abstract: The American Recovery and Reinvestment Act passed by the U.S. government in 2009 mandates that all healthcare organizations adopt a certified electronic health record (EHR) system by 2015. Failure to comply will result in Medicare reimbursement penalties, which steadily increase with each year of delinquency. There are several repercussions of this seemingly top-down, rule-bound organizational change-one of which is employee resistance. Given the penalties for violating EHR meaningful use standards are ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…Previous research indicates that clinician satisfaction with HIT is mixed, which may be related to clinical documentation practice, workload, and productivity [ 45 ]. Physicians have reported dissatisfaction with template-based HIT documentation [ 45 ], possibly due to their high autonomy needs to prioritize work tasks [ 46 ]. In the current study, nurses also expressed dissatisfaction with template-based physical assessment because documentation was not streamlined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that clinician satisfaction with HIT is mixed, which may be related to clinical documentation practice, workload, and productivity [ 45 ]. Physicians have reported dissatisfaction with template-based HIT documentation [ 45 ], possibly due to their high autonomy needs to prioritize work tasks [ 46 ]. In the current study, nurses also expressed dissatisfaction with template-based physical assessment because documentation was not streamlined.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study that aimed to understand physicians’ and nurses’ experience with EHRs found no major perceived differences based on profession [ 48 ]. A commonality among all professions appears to be the need for communication when implementing new HIT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, personal computers came with many preinstalled applications so that consumers could start using their new machines “out-of-the-box.” The net effect is that state-of-the-art information platforms’ minimum feature sets encompass multiple generations of earlier innovations as a technology matures. It is likely that EHR vendors followed a similar pattern of increased technological sophistication as a matter of normal business prior to 2006 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A leader in this realm, Lupton (1994) promoted theoretical and methodological practices for interrogating the power dynamics inherent to health-related issues. Meanwhile, the cybernetic tradition attends to organizational and systemic dynamics, such as those occurring in online social support groups (Wright, 2016) and healthcare organizations (Barrett, 2018). Those teaching from a phenomenological perspective seek understanding of how persons live and articulate their health experiences.…”
Section: Foundationsmentioning
confidence: 99%